Transplanted photoreceptor precursors transfer proteins to host photoreceptors by a mechanism of cytoplasmic fusion - Singh, M; Balmer, J; Barnard, A; Aslam, S; Moralli, D; Green, C; Barnea-Cramer, A; Duncan, I; MacLaren, R (Nature Publishing Group, 2016)
Photoreceptor transplantation is a potential future treatment for blindness caused by retinal degeneration. Photoreceptor transplantation restores visual responses in end-stage retinal degeneration, but has also been assessed in non-degenerate retinas. In the latter scenario, subretinal transplantation places donor cells beneath an intact host outer nuclear layer (ONL) containing host photoreceptors. Here we show that host cells are labelled with the donor marker through cytoplasmic transfer-94±4.1% of apparently well-integrated donor cells containing both donor and host markers. We detect the occurrence of Cre-Lox recombination between donor and host photoreceptors, and we confirm the findings through FISH analysis of X and Y chromosomes in sex-discordant transplants. We do not find evidence of nuclear fusion of donor and host cells. The artefactual appearance of integrated donor cells in host retinas following transplantation is most commonly due to material transfer from donor cells. Understanding this novel mechanism may provide alternate therapeutic strategies at earlier stages of retinal degeneration.